歯肉出血を契機に発見された後天性第Ⅹ因子欠乏症の1例 - 高山, 智宏; 雨河, 茂樹; 橘川, 芳明; 小川, 芙美; 吉濱, 直哉; 大西, 徹郎 (日本口腔外科学会雑誌, 2018)
Factor X deficiency is a coagulation disorder caused by lack of factor X, which is a vitamin K-dependent clotting factor synthesized in the liver. The disease can be inherited or acquired. This case report describes a male patient who was given a diagnosis of acquired factor X deficiency after having gingival bleeding. [Case and Progress] An 80-year-old man had undergone detailed examinations for the cause of anemia in another hospital. Hemorrhagic lesions were not found, and gingival bleeding was suspected as the cause of anemia. Therefore, he visited our hospital for further evaluation of gingival bleeding. Because gingival bleeding was caused by periodontal disease, we extracted the right mandibular second molar and left maxillary second molar under local anesthesia. Because of persistent intermittent gingival bleeding, we referred the patient to a hematologist. The blood examination revealed prolonged prothrombin time and decreased factor X activity, and he was given a diagnosis of acquired factor X deficiency on the basis of his past medical history. Although we performed local hemostatic treatment and medical therapy, it took us about 40 days to arrest the hemorrhage.